Patli lambi kitab - Sami, Mustafa; Mahreen, Zuberi (book group Karachi, 2016)
"Patli Lambi Kitab" is a popular Urdu children's book series published by Book Group. It's designed for young readers, typically aged 8-9, and aims to foster a love for reading and learning.